Quasicrystalline 30° twisted bilayer graphene: fractal patterns and electronic localization properties - Vidarte, Kevin J. U.; Lewenkopf, Caio (Frontiers in Carbon, 2024)
The recently synthesized 30 • twisted bilayer graphene (30 • -TBG) systems are unique quasicrystal systems possessing dodecagonal symmetry with graphene's relativistic properties. We employ a real-space numerical atomistic framework that respects both the dodecagonal rotational symmetry and the massless Dirac nature of the electrons to describe the local density of states of the system. The approach we employ is very efficiency for systems with very large unit cells and does not rely on periodic boundary conditions. These features allow us to address a broad class of multilayer two-dimensional crystal with incommensurate configurations, particularly TBGs. Our results reveal that the 30 • -TBG electronic spectrum consist of extended states together with a set of localized wave functions. The localized states exhibit fractal patterns consistent with the quasicrystal tiling.